Detection of bovine herpesvirus 5 (BoHV-5) in formalin-fixed, paraffin-embedded bovine brain by nested PCR in Colombian cattle - Pedraza, Francisco J. [UNESP]; Alessi, Antonio C. [UNESP]; Barbosa-Stancioli, Edel F. (Univ Antioquia, Fac Ciencias Agrarias, 2010)
Fifteen cases of viral meningoencephalitis in Colombian cattle were tested by nested PCR analysis for the detection of bovine herpesvirus 5 (BoHV-5). All fatal cases had shown severe neurological signs and had occurred following natural outbreaks of the disease. The neurological infection was histologically characterized by mild to moderate inflammatory changes in the brain and cerebellum, including meningitis, mononuclear perivascular cuffing, gliosis, haemorrhage, and the presence of Gitter cells (macrophages) accompanying large areas of malacia. No intranuclear inclusion bodies were seen in any of the cases. Results from BoHV-5 molecular extraction analyses showed there were five positive cases thus confirming the presence of the virus in Colombia.

Quinze casos de meningoencefalite viral em gado bovino Colombiano foi analisado pela reação em cadeia da polimerasa (PCR) para a detecção do herpesvírus bovino 5 (BoHV-5). Todos os casos mostraram graves sinais neurológicos antes de morrer y aconteceram como surtos naturais da doença. A infecção neurológica foi caracterizada histologicamente por leves a moderados câmbios inflamatórios no cérebro e cerebelo, incluindo meningite, manguitos perivasculares, gliose, hemorragia e a presencia de células gitter (macrófagos) acompanhando grandes áreas de malacia. Não se encontraram corpos de inclusão intranucleares em nenhum dos casos. Os resultados da análise da extração molecular do BoHV-5 por PCR revelaram a existência de cinco casos positivos, os quais confirmam a presença do vírus na Colômbia.
Detecção de herpesvírus bovino 5 (BoHV-5) em cérebro incluído em parafina e fixado em formalina, pela PCR, em bovinos colombianos
Keywords: bovine herpesvirus; polioencephalomalacia; Viral encephalitis